SUNFISH, MOLA MOLA (L) A NEW RECORD FROM INDIAN WATERS - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
The sunfish, Mola mola (L), is recorded for the first time from Indian waters. Various body measurements of the single specimen caught from Satpati, Bombay, are given.